Priorities for the effective implementation of osteoarthritis management programs: an OARSI international consensus exercise. Issue 9 (September 2019) - ,; Quicke, J.; Skou, S.T.; Risberg, M.A.G.; Roos, E.M.; Thorstensson, C.; Hurley, M.; Nelson, A.; Jinks, C.; Briggs, A.; Egerton, T.; Allen, K.; et al.
Summary: Objective: The Joint Effort Initiative was endorsed by Osteoarthritis Research Society International (OARSI) in 2018 as a collaboration between international researchers and clinicians with an interest in the implementation of osteoarthritis management programs (OAMPs). This study aimed to identify and prioritise activities for future work of the Joint Effort Initiative. Design: A survey was emailed to delegates of the 2018 OARSI World Congress attending a pre-conference workshop or with a known interest in OAMPs ( n  = 115). Delegates were asked about the most important issues regarding OAMP implementation. The top 20 issues were synthesised into 17 action statements, and respondents were invited to participate in a priority ranking exercise to determine the order of importance of the statements. Results: Survey respondents ( n  = 51, 44%) were most commonly female (71%), with an allied health background (57%), affiliated with universities (73%) from Oceania (37%), and Europe/UK (45%). The five highest ranked action statements were: i) Establish guidelines for the implementation of different OAMP models to ensure consistency of delivery and adherence to international best practice. ii) Develop and assess training and education programs for health care professionals (HCPs) delivering OAMPs. iii) Develop and evaluate the implementation and outcomes of novel models of OAMPs. iv) Develop and assess core skill sets and resources for HCPs delivering OA care. v) Develop a framework for enhancing the quality of care provided by OAMPs. Conclusion: Prioritising statements will bring focus to the future work of the Joint Effort Initiative in the future and provide a basis for longer-term actions.